Enhancing persuasive writing skills through ecology-themed communicative poster-based instruction in secondary school - Ratnawati Ratnawati; Tarman Tarman (Journal of Environment and Sustainability Education, 2026)
This study examined the effect of a communicative poster-based approach in teaching ecology-themed persuasive texts on the writing skills of 32 Grade VIII students at a secondary school in Makassar, Indonesia, under the Independent Curriculum. A pre-experimental one-group pretest-posttest design was employed; data were collected through persuasive writing tests and scored with analytic rubrics. Results revealed a significant improvement in mean scores from 63.75 to 81.25 (p = 0.000), with a very large effect size of 2.20 (Cohen, 1988). Integrating environmental themes with communicative language instruction through poster creation effectively developed students' persuasive writing skills. Ecology-based topics may also foster environmental awareness as a secondary outcome, though this remains an inference rather than a directly measured variable.